ANALISIS PENGEMBANGAN SISTEM EVALUASI PENDIDIKAN BERDASARKAN NILAI-NILAI AL QUR’AN: KAJIAN KONSEPTUAL DAN IMPLEMENTASI - Mohammad Nurul Burhan; Ulfa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine and formulate the concept of developing an educational evaluation system based on the values of the Qur'an. The method used is library research with a qualitative descriptive approach. Data sources consist of primary and secondary literature, including Qur'anic exegesis, hadith, books, and relevant scientific journal articles. Data collection techniques employed documentation, while data analysis used content analysis. The findings show that: (1) The concept of evaluation in the Qur'an is reflected through terms such as al-bala' (trial), al-hisab (calculation), al-hukm (judgment), al-qadha (decree), and al-nazhr (observation); (2) The principles of evaluation based on Qur'anic values include monotheism, justice, continuity, comprehensiveness, objectivity, responsibility, integration, cooperation, practicality, and balance; (3) The human typology in QS. Fathir verse 32 (zhâlimun linafsih, muqtashid, sâbiqun bil khairât) can serve as a reference for character evaluation; (4) The integration of Qur'anic values in the cognitive, affective, and psychomotor domains produces holistic evaluation; (5) The development model of the evaluation system includes the stages of planning (takhthith), implementation (tathbiq), processing (tahlil), and reporting and follow-up (taqrir wa mutaba'ah). In conclusion, the educational evaluation system based on Qur'anic values is holistic and transcendental, and can serve as an alternative paradigm in the development of Islamic education evaluation in the modern era.